Sztuczna inteligencja na kulturowym rozdrożu. W poszukiwaniu równowagi między innowacją a sprawiedliwością algorytmiczną .......... 455 - Ożegalska-Łukasik, Natalia (Peregrynacje międzykulturowe: Księga jubileuszowa dedykowana prof. Tadeuszowi Palecznemu, 2025)
ARTIFICIAL INTELLIGENCE AT A CULTURAL CROSSROADS: SEARCHING FOR A BALANCE BETWEEN INNOVATION AND ALGORITHMIC FAIRNESS This essay critically examines the socio-cultural implications of the development of generative artificial intelligence (AI), with particular emphasis on the reproduction of social inequalities in the digital space. Starting from a social constructivist perspective, the text analyses how AI systems, being the product of specific cultural contexts and power structures, can unwittingly replicate and reinforce existing social hierarchies and dominant narratives. The author analyses the various dimensions of the problem of discrimination in AI, pointing to overlapping categories of exclusion related to gender, race, social class and ethnicity. Particular attention is paid to the processes of reproduction of cultural capital in the context of the selection of training data and the influence of dominant discourses on the formation of the “personality” of AI systems. The empirical part presents case studies illustrating the mechanisms of exclusion in currently functioning systems and their social consequences. The essay ends with a reflection on future challenges in the context of the growing role of AI in shaping cultural communication, calling for the democratization of the process of AI development, and emphasizing the role of social participation and decolonization of knowledge in shaping more equitable technologies of the future.